2015
DOI: 10.1002/masy.201400166
|View full text |Cite
|
Sign up to set email alerts
|

Aryleneethynylene Trimers Bearing Calix[4]arenes: Synthesis, Optical Properties and Self‐Assembling Studies

Abstract: Summary: New homoditopic bis-calix [4]arene-carbazole conjugates, armed with hydrophilic carboxylic acid functions at their lower rims, are disclosed. Evidence for their self-association in solution was gathered from solvatochromic and thermochromic studies, as well as from gel-permeation chromatography analysis. Their ability to function as highly sensitive sensors toward polar electron-deficient aromatic compounds is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Materials CCC-1, 13 CCC-2 13 and CCC-3 14 were synthesized according to our reported procedures and fully characterized by FT-IR, 1 H/ 13 C NMR, and microanalysis. Cytochrome c from equine heart ($95% (SDS-PAGE), Aldrich C2506), myoglobin from equine heart ($90% (SDS-PAGE), Aldrich M1882), lysozyme from chicken egg white ($90%, Aldrich L6876) were purchased from Sigma-Aldrich Corp., EUA, and used as received.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Materials CCC-1, 13 CCC-2 13 and CCC-3 14 were synthesized according to our reported procedures and fully characterized by FT-IR, 1 H/ 13 C NMR, and microanalysis. Cytochrome c from equine heart ($95% (SDS-PAGE), Aldrich C2506), myoglobin from equine heart ($90% (SDS-PAGE), Aldrich M1882), lysozyme from chicken egg white ($90%, Aldrich L6876) were purchased from Sigma-Aldrich Corp., EUA, and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…1), both armed with hydrophilic carboxylic acid functions at their lower rims but differing on the type of substitution at the carbazole rings. 13 It was demonstrated that these uorophores are able to function as highly sensitive sensors toward electron-decient aromatic compounds (picric acid and 2,4,6-trinitrotoluene) used in explosives' compositions in solution as well as serve as structural motifs in the construction of supramolecular polymers in organic solution phase. 13 These new synthetic receptors were also designed having in mind their potential as biosensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation